THE DETECTION OF QUARKS IN DIFFUSE NEBULAE - MENDEZ, ME; CARRASCO, L (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1971)
The problem of detecting quarks in diffuse nebulae is studied, considering the existence of hydrogenic quark atoms. It is shown that the predicted upper limit of abundance, relative to hydrogen, is 1.5 X 10^8 if tne infrared lines produced by the quark at
BOL OBS TONAN TACUB
Keywords: DETECTION, QUARKS, DIFFUSE NEBULAE; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS